2023
DOI: 10.1039/d2cp04884a
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization of opening and closing of two gramicidin A channels pulled together by a linker: possible relevance to channel clustering

Abstract: The linear 15-mer peptide gramicidin A (gA) produced by Bacillus brevis is known to form the simplest natural ion channel in lipid membranes representing a head-to-head transmembrane dimer. Its incorporation...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[24] Furthermore, once two gA channels are connected by a linker, their lifetime will be significantly increased. [25][26][27] Cholesterol (CHOL), as a major lipid component of plasma membranes of mammalian cells, exhibits significant impact on the conformation and activity of a variety of ion channels. [28][29][30][31][32][33][34] For gA, some experimental studies have shown that gA channel inactivation occurs in CHOLcontaining erythrocyte membranes and the rate of channel inactivation is strongly dependent on the phospholipid-to-CHOL molar ratio in the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Furthermore, once two gA channels are connected by a linker, their lifetime will be significantly increased. [25][26][27] Cholesterol (CHOL), as a major lipid component of plasma membranes of mammalian cells, exhibits significant impact on the conformation and activity of a variety of ion channels. [28][29][30][31][32][33][34] For gA, some experimental studies have shown that gA channel inactivation occurs in CHOLcontaining erythrocyte membranes and the rate of channel inactivation is strongly dependent on the phospholipid-to-CHOL molar ratio in the membrane.…”
Section: Introductionmentioning
confidence: 99%